До питання про історіографію досліджень з історії діяльності Чернігівської класичної чоловічої гімназії у XІX-XX столітті - Рига, Д. (Сiверянський лiтопис, 2018)
У статті мова йде про питання історіографії досліджень з історії Чернігівської
класичної чоловічої гімназії у XІX-XX столітті. В статье идет речь о исследованиях историографических вопросов по истории
создания и деятельности Черниговской классической мужской гимназии в XІX-XX веке. Chernihiv classical male gymnasium among the educational institutions of the XIX –
early XX century, occupied one of the leading places in the educational process in Chernihiv
region. This article will address the disclosure of important issues that are still not adequately
covered. This is especially true of the disclosure of an important issue of the historiography of
studies on the history of the Chernihiv Classical Male Gymnasium in the XIX-XX centuries.
Given this perspective, it is expedient to consider the historical heritage of gymnasium
education of Chernihiv Region, which led to the choice of the topic of the article: «On the
question of the historiography of research, on the history of the Chernihiv classical male
gymnasium in the XIX-XX century», which is actually devoted to the analysis of the problem
of development and formation gymnasium education in Chernigov region XIX – beginning.
XX century, in general, the history of the Chernihiv classical male gymnasium, in particular.
The history of the formation and development of gymnasium education and the Chernihiv
classical male gymnasium, in particular – were interested in domestic researchers in different
historical periods. By studying this topic, various degrees of its scientific elaboration were
discovered: both by foreign and domestic researchers of the past.
The historiography of gymnasium education in Chernihiv can be described in two ways:
on the one hand, there is a large number of scientific works, where the main organizational
and content characteristics of the activity of the Chernihiv classical male gymnasium are
analyzed to a depth of depth in the period under study; On the other hand, the overwhelming
majority of the authors turned to the analysis of the development of gymnasium education
in Chernihiv region – from a purely historical, rather than a historical and pedagogical side,
which complicates the process of studying the pedagogical experience of this educational
establishment in the nineteenth century. Twentieth century
The problem of formation and development of gymnasium education in Chernihiv region
is still the subject of research by famous historians – teachers of the present.
Despite the large number of scientific works, the following issues remained open:
the principle of continuity between the levels of education in the period under study, the
peculiarities of leadership in education in Chernihiv, and the educational activities of
outstanding educators in the Seversk region.
The analysis of scientific works on the given subject gives all grounds to assert that at
present there is no such scientific research, where the historiography of the formation and
development of the Chernihiv classical male Alexander’s gymnasium, in particular, in this
historical period, would be systematically and fully analyzed.
Studying the state of gymnasium education in Chernihiv region, we collected a large
number of scientific works that allow us to understand only some aspects of this problem.